Analysis and Simulation of the Schottky Junction Using an Ensemble Monte Carlo Model - Fatemeh Haddadan; Mohammad Soroosh; Ramakrishnan Rajasekar (Journal of Optoelectronical Nanostructures)
<!-- [if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!-- [if gte mso 9]> <w:LsdExceptio